n-Butyldichlorido(2-{(1E)-1-[2-(pyridin-2-yl)hydrazin-1-ylidene]ethyl }phenolato)tin(IV) - Abu Affan, M.; Chee, D.N.A.; Ahmad, F.B.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent molecules comprise the asymmetric unit of the title compound, [Sn(C4H9)(C13H12N3O) Cl-2]. The Sn atom in each is coordinated by the tridentate ligand via the phenoxide O, hydrazine N and pyridyl N atoms, forming five- and six-membered chelate rings. The approximately octahedral coordination geometry is completed by the alpha-C atom of the n-butyl group (which is trans to the hydrazine N atom) and two mutually trans Cl atoms. Differences between the molecules are evident in the relative planarity of the chelate rings and in the conformations of the n-butyl groups [C-C-C-C = 177.2 (5) and -64.4 (11)degrees]. Significant differences in the Sn-Cl bond lengths are related to the formation of N-H center dot center dot center dot Cl hydrogen bonds, which link the molecules comprising the asymmetric unit into dimeric aggregates. These are consolidated in the crystal packing by C-H center dot center dot center dot Cl contacts. The structure was refined as an inversion twin; the minor twin component is 37 (3)%.